Lithium toxicity in a neonate. Issue 7 (July 1983) - Morrell, P; Sutherland, G R; Buamah, P K; Oo, M; Bain, H H
Abstract : Severe transplacental lithium toxicity in a neonate is described. There were gross functional lesions of the cardiovascular, renal, and neuromuscular systems with no structural abnormalities. At 1 year of age cardiovascular and renal function is normal, but there is developmental delay.